Pelatihan Pemasaran Berbasis Media Sosial untuk Peningkatan Penjualan Produk Lokal di Desa Waitatiri, Maluku Tengah: Pengabdian - H. Sitaniapessy, Rainier; E. Huwae, Victor; J. Saununu, Siska; Tubalawony, Jacsy; A. Kurniawan, Sabda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community Service (PKM) activities entitled "Social Media-Based Marketing Training to Increase Sales of Local Products in Waitatiri Village, Central Maluku" were held at Sopapei Suli Beach, Central Maluku on May 12, 2025, with the aim of improving the quality of MSME product marketing through product photo strategies and making online flyers and short videos. The methods used include socialization, training, practical workshops, discussions, evaluations, and reporting. Participants were trained in simple photography techniques using smartphones, making catalogs and flyers to be used for online promotions on social media. The results of the activity showed that participants were able to produce quality product photos, make catalogs and promotional flyers and short videos, and start implementing simple branding in their businesses. In addition, participants were encouraged to utilize social media and digital marketplaces in expanding product marketing. The application of simple technology and creative innovation is expected to increase the competitiveness of local MSME products in a wider market. This activity has a positive impact on the development of social media marketing and it is recommended to carry out further assistance and institutional support to strengthen the sustainability of the program.